Trade Union Recognition and the Concepts of ‘Workplace’ in South Africa and the ‘Appropriate Bargaining Unit’ in Canada: Some Comparative Insights into Bargaining Constituencies and Protection of Minority Interests - Germishuys-Burchell, Wilhelmina (Comparative and International Law Journal of Southern Africa, 2025)
This article identifies challenges surrounding the legal regulation of trade union recognition with specific reference to the concept of ‘workplace’ as the constituency within which the majority rules. The definition of ‘workplace’ in the South African Labour Relations Act 66 of 1995 creates the potential for minority interests to be ignored and hinders even majority unions seeking recognition, especially where the workplace is dispersed across different locations. This predicament, and the harsh effect and potential dangers of excluding minority voices in the labour context, has also been recognised by the Constitutional Court. This article considers two factors central to Canada’s independently determined ‘appropriate bargaining unit’: accommodating special or significant minority interests and addressing recognition in the context of multi-location employers. Although the Canadian legal system (like the South African one) favours majority unions, this article seeks to show Canadian law shows greater awareness of the potential unfairness of unqualified or misapplied majoritarianism. It highlights Canada’s independently determined bargaining unit as the constituency for majority rule and concludes that this model may offer a more appropriate framework for South Africa.